Die James-Bond-Story - Hunt, Chris (BR, 1999)
"The James Bond Story" is a celebration of the most enduring of all action heroes. It includes interviews with all the actors to have played Bond on the big screen - Sean Connery, George Lazenby, Roger Moore, Timothy Dalton and Pierce Brosnan. Chris Hunt's programme sets out to penetrate the cover of the celebrity spy. What makes James Bond the supreme secret agent? Why do all men want to be him and all women want to sleep with him? Like a Bond movie, Christ Hunt's documentary is extravagantly filmed. The beautiful women who discuss Bond's sexism and sexuality are Jane Seymour, Maud Adams and Mariella Frostrup. Jamaica, Los Angeles and Geneva are among the exotic locations visited and, from Q's arsenal, there are fast cars and gadgets to satisfy the most avid of technophiles. Clips from each of the nineteen official Bond films - some twenty-five minutes - keep the "kiss, kiss, bang, bang" action moving at a rip roaring pace. [www.abc.net.au]